INDIKASI TAFSÎR AL-'ILMÎ DALAM TAFSIR AL-IBRÎZ KARYA BISRI MUSTHAFA - Muhammad Mufid Muwaffaq (UIN Siber Syekh Nurjati Cirebon, 2020)
Al-Ibriz li Ma’rifati Tafsir al-Qur’an al-‘Aziz by a traditionalist KH Bisri Musthafa has numerous scientific-nuanced interpretation, a nuance that basically is typical to modernist. Closely reading Kiai Bisri’s academic background and journey, this article found a particular period of study that could explain this uniqueness. This period lasted about one year. In that year Kiai Bisri went on Hajj (pilgrimage) while studying in Mecca and Medina. He did because of the demand for mastery of religious insight given by father’s-in-law boarding school in Kasingan. In Mecca and Medina, Kiai Bisri study with several professors and knew the big names who lived in the same period. Among these big names, there are Muhammad ‘Abduh and Tantawi Jawhari This period instills to him a more rational way of comprehending Islam and Islamic texts. Kiai Bisri read works of Muhammad ‘Abduh and Tantawi Jawhari which are almost associated to scientific interpretation to tafsir al-‘ilm). Looking at the cosmopolitan Mecca and Medina at the time, it was not difficult to imagine that Kiai Bisri was affected by some of the innate attitude of the cosmopolitan environment, namely rationality and closeness to modern science. Perhaps was what inspired Kiai Bisri to conduct a study with his discussion partners, he returned from Mecca and Medina. In this discussion, several scientific-oriented commentaries, including the two modernist figures, were also studied.. This might be an explains of Kiai Bisri’s life that explains the existence of scientific-nuanced interpretation.